Clinical case report on treatment of Listeria monocytogenes meningoencephalitis: Intrathecal injection. Issue 9 (1st August 2018) - Pan, Xu‐Biao; Wang, Zhi‐Xin; Ma, Ming‐He; Wang, Hong‐Bin; Gan, Gui‐Fen; Fan, Hai‐Ning
Key Clinical Message: This article mainly reports the process of clinical diagnosis and treatment of a misdiagnosed Listeria monocytogenes meningoencephalitis. The patient's condition is aggravated because of the ineffective prophase therapy. In the later stage, we were mainly through combined antibiotics and given proper routes of administration, so that patient can recover quickly. Abstract : This is the head CT of a patient with listeria monocytogenes meningoencephalitis. It describes the complete change of brain lesions from the onset stage to the 1 months after the cure. The red arrows shows obvious dilatation of the bilateral ventricular, esp in the posterior corner of the temporal region and the surrounding brain interstitial edema as indicated by the blue arrows.